2008
DOI: 10.1111/j.1742-1241.2007.01678.x
|View full text |Cite
|
Sign up to set email alerts
|

An ABC of apolipoprotein C-III: a clinically useful new cardiovascular risk factor?

Abstract: Targeting apoC-III metabolism may therefore be an important, new therapeutic approach to managing dyslipidaemia and CHD risk in obesity, insulin resistance and type 2 diabetes mellitus. However, further work is required to establish the practical aspects of measuring apoC-III in routine laboratory service and the precise therapeutic targets for serum total apoC-III and/or apoC-III in apoB-containing lipoproteins. While showing much promise as a potentially useful cardiovascular risk factor, apoC-III is not yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
64
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 91 publications
3
64
0
3
Order By: Relevance
“…*n = 8 for these values. to be enhancement of LPL activity and enhanced hepatic uptake of TRL (10,11,20). Of note, the reduction in TG noted in this study was not associated with increases in LDL-C, as often seen with TG-lowering therapies.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…*n = 8 for these values. to be enhancement of LPL activity and enhanced hepatic uptake of TRL (10,11,20). Of note, the reduction in TG noted in this study was not associated with increases in LDL-C, as often seen with TG-lowering therapies.…”
Section: Discussionmentioning
confidence: 63%
“…ApoC-III affects TG metabolism by inhibiting lipoprotein lipase (LPL) activity and by interfering with receptor-mediated uptake of TRLs by the liver (10,11). Mice overexpressing apoC-III not only have high plasma TG but also display increased insulin resistance (12).…”
mentioning
confidence: 99%
“…ApoCIII is known to be an important link between glycaemia and dyslipidaemia [22] as its expression is induced by high glucose levels and is responsive to insulin. However, whilst several studies have shown that higher apoCIII content on lipoproteins is associated with their atherogenicity [23,24], the association of total circulating apoCIII itself with CVD has had less investigation [21]. One of the largest studies is the Hoorn study [25].…”
Section: Discussionmentioning
confidence: 99%
“…ApoCIII inhibits the catabolism of triacyglycerolrich lipoproteins, partly through inhibition of their hepatic uptake and partly through inhibition of lipoprotein lipase activity. ApoCIII non-specific gene deletion in animal models is associated with premature atherosclerosis [20], and most studies suggest a likely pro-atherogenic role [21]. ApoCIII is known to be an important link between glycaemia and dyslipidaemia [22] as its expression is induced by high glucose levels and is responsive to insulin.…”
Section: Discussionmentioning
confidence: 99%
“…ApoC-III has been associated with hypertriglyceridemia ( 19,20 ), increased cardiovascular risk ( 21 ), atherosclerosis in animal models ( 22 ), and subclinical atherosclerosis (increased coronary artery calcium) in humans ( 2 ).…”
Section: Discussionmentioning
confidence: 99%